From Space to Stage: How Interactive Screens Will Change Urban Life. - Kuikkaniemi, Kai; Jacucci, Giulio; Turpeinen, Marko; Hoggan, Eve; Müller, Jörg (Computer (00189162), 2011)
Framed digital displays will soon give way to walls and facades that creatively motivate individual and group interaction. A stage serves as an apt metaphor to explore the ways in which these ubiquitous screens can transform passive viewing into an involved performance.